Effects of long-term care insurance on health: a study of the middle-aged and older adult in pilot cities in China - Chen, Qian; Ma, Sang; Lyu, Xinyue (Frontiers in Public Health, 2025)
BackgroundChina established a trial long-term care insurance program in 15 cities in 2016 to address the country’s aging population; however, the policy’s impacts must be confirmed.MethodsPanel data from the China Health and Retirement Longitudinal Study (CHARLS) were used, covering four periods: 2011, 2013, 2015, and 2018. A difference-in-difference model was applied to analyze the impact of the long-term care insurance policy on health status, comparing residents in pilot cities with those in non-pilot cities.ResultsThe implementation of long-term care insurance in pilot cities led to a significant increase in self-rated health of 0.093 levels among surveyed residents compared to those in non-pilot cities. Significant variables included educational attainment, household registration, marital status, and the regional number of hospitals. Additionally, the health condition of citizens in central and western pilot cities improved considerably compared to those in eastern pilot cities.ConclusionThe long-term care insurance policy has a significant positive effect on the health status of residents, demonstrating its potential as a valuable policy tool to address health challenges associated with an aging population.